Key concepts in media and communications / Paul Jones and David Holmes - "Jones, Paul"; Hlmes, David (New Delhi, 2012)
This book covers the key concepts central to understanding recent developments in media and communications studies. Wide-ranging in scope and accessible in style it sets out a useful, clear map of the important theories, methods, and debates. The entries critically explore the limits of a key concept as much as the traditions that define it. They include clear definitions, are introduced within the wider context of the field and each one is fully cross-referenced, is clearly illustrated with relevant examples, and provides a guide to further reading and an index.
Keywords: Communication